A new donor for charge-transfer systems: synthesis and properties of 2, 4, 7, 9-tetramethyl-1, 6-dithiapyrene (TMDTP) and structure of (TMDTP)3(PF6)2·2THF and TMDTP–TCNQ. Issue 24 (20th April 2021) - Bendix, Jesper; Bechgaard, Klaus; Christensen, Jørn Bolstad
Abstract : The heterocyclic donor molecule 2, 4, 7, 9-tetramethyl-1, 6-dithiapyrene (TMDTP) has been synthesized in five steps. The charge-transfer complex, TMDTP–TCNQ, has been prepared and the salt, (TMDTP)3 (PF6)2 ·2THF, obtained by electrocrystallization. Abstract : The heterocyclic donor molecule 2, 4, 7, 9-tetramethyl-1, 6-dithiapyrene (TMDTP) has been synthesized in five steps. Oxidation of TMDTP is facile ( E 1 1/2 = 0.27 V and E 2 1/2 = 0.79 V vs. SCE). The charge-transfer complex, TMDTP–TCNQ, has been prepared and the salt, (TMDTP)3 (PF6 )2 ·2THF, obtained by electrocrystallization. The structure of TMDTP, TMDTP–TCNQ and (TMDTP)3 (PF6 )2 ·2THF has been characterized by X-ray crystallography and computationally.